Adding years to life: effect of avoidable mortality on life expectancy at birth. Issue 4 (August 1992) - Benavides, F G; Orts, R; Pérez, S
Abstract : STUDY OBJECTIVE–The aim was to determine the number of years that could be gained by preventing avoidable deaths. DESIGN–The study arose from the concept of avoidable causes of death and life expectancy at birth. Four abbreviated life tables were computed. The first included all causes of death; the second excluded all avoidable causes of death; the third and fourth excluded respectively primary and secondary avoidable causes of death. SETTING–Mortality and population data were taken from Mortality Statistics Offices in Valencia Region, Spain. MAIN RESULTS–Life expectancy at birth (LEB) was 75.7 years. After removing all avoidable deaths, LEB increased by 1.74 years. This improvement is attributed to avoidable deaths by primary prevention (1.09 years) and avoidable death by secondary prevention (0.37 year). CONCLUSIONS–According to these results the greatest improvement in LEB would be gained by primary prevention.